Effects of Probucol on plasma amyloid-β transport in patients with hyperlipidemia: a 12-week randomized, double-blind, placebo-controlled trial - Liangjun Dang; Shan Wei; Yi Zhao; Rong Zhou; Suhang Shang; Fan Gao; Jingyi Wang; Jin Wang; Qiumin Qu (Lipids in Health and Disease)
Abstract Background Although dyslipidemia has been acknowledged as a risk factor for Alzheimer’s disease (AD), the effects of lipid-lowering drugs on AD have not been determined. The primary pathophysiological hallmark of AD is the deposition of amyloid-β (Aβ) plaques in the brain. Plasma Aβ levels are influenced by the transport of Aβ from the central nervous system to the peripheral blood. This study investigates the effects of Probucol, a lipid-lowering and antioxidant drug, on plasma Aβ transport. Methods A total of 120 hyperlipidemic patients with normal cognition were randomly assigned (1:1 ratio) to receive either Probucol (1000 mg daily for 12 weeks) or a placebo. Plasma Aβ, soluble receptor of advanced glycation end products (sRAGE), and fasting lipid profiles were measured at baseline and every 6 weeks. Results A total of 108 participants completed the study, with 55 in the Probucol group. The cohort consisted of 58 (53.7%) women, with a mean age of 58.4 ± 8.0 (range, 45–80) years. After 12 weeks of treatment, the changes in plasma Aβ42 and sRAGE levels significantly differed between the Probucol and placebo groups (ΔAβ42: β = 6.827, P = 0.030; ΔsRAGE: β = 98.668, P = 0.004). Furthermore, ΔsRAGE was positively correlated with the change in Aβ42 (β = 0.018, P = 0.048). When adjusted for ΔsRAGE, the effect of Probucol on plasma Aβ42 levels was attenuated (β = 5.065, P = 0.116). In the Probucol group only, ΔsRAGE was significantly correlated with oxidized low-density lipoproteins (β = 4.27, P = 0.011), total cholesterol (β = 67.50, P = 0.046), and low-density lipoproteins (β = − 91.01, P = 0.011). Conclusions Daily oral administration of Probucol (1000 mg) for 12 weeks significantly increased plasma Aβ42 levels, likely through modulation of sRAGE. This effect may be attributed to the antioxidant and lipid-lowering properties of Probucol. These findings suggest that Probucol could potentially serve as a protective agent against the pathological processes of AD. Trial registration This study was registered on the Chinese Clinical Trial Registry platform in June 2019 (Trial registration number: ChiCTR-1900023542).